Solid Ammonium Nitrate Aerosols as Efficient Ice Nucleating Particles at Cirrus Temperatures. Issue 8 (15th April 2020) - Wagner, Robert; Bertozzi, Barbara; Höpfner, Michael; Höhler, Kristina; Möhler, Ottmar; Saathoff, Harald; Leisner, Thomas
Abstract: Recent satellite observations and high‐altitude aircraft measurements have demonstrated the presence of solid ammonium nitrate particles in the Asian monsoon upper troposphere. Most likely, these particles are formed by a heterogeneous crystallization mechanism, given that efflorescence is strongly inhibited for pure ammonium nitrate solution droplets. Crystallization can be induced by the presence of ammonium sulfate, which more easily crystallizes and serves as a heterogeneous nucleus for the crystallization of ammonium nitrate. In the present study, we have investigated this crystallization pathway for different amounts of ammonium sulfate admixed to ammonium nitrate solution droplets and measured the heterogeneous ice nucleation ability of the crystallized particles at cirrus temperatures in a cloud chamber and with a continuous flow diffusion chamber. We found that an admixture of only 0.6 mol% of ammonium sulfate was sufficient to induce the crystallization of ammonium nitrate at 223 K and 22% RHw . These almost pure, crystalline ammonium nitrate particles showed the same temperature‐dependent ice nucleation behavior as observed for other inorganic salts like ammonium sulfate and sodium chloride. At temperatures above 230 K, the crystalline ammonium nitrate particles first deliquesced and nucleated ice homogeneously at ice saturation ratios between about 1.45 and 1.50. Below 230 K, heterogeneous ice nucleation was observed to start at an ice saturation ratio as low as 1.13. The deduced ice nucleation active surface site densities were in the range from 10 10 –10 11 m −2 at ice saturation ratios between 1.2 and 1.4, thus similar in magnitude to those of desert dust particles. Key Points: Crystallization of ammonium nitrate solution droplets can be induced by the admixture of very small amounts of ammonium sulfate Crystalline ammonium nitrate particles induce heterogeneous ice nucleation at temperatures below 230 K Ice nucleation active surface site densities of crystalline ammonium nitrate particles are comparable in magnitude to those of desert dust